29. Impaired VEP after photostress in migraine patients between attacks. Issue 1 (January 2015) - Coppola, G.; Di Lenola, D.; Bracaglia, M.; Di Ciaccia, G.; Di Lorenzo, C.; Serrao, M.; Parisi, V.; Pierelli, F.
<x xml:space="preserve">Abstract</x> Subtle impaired macular vision was observed among different psychophysical experimental tasks in migraine. Here we studied visual evoked potential (VEP) after photostress (PS) representing an objective index of the dynamic properties of macular performance after exposure to intense light stimulation. We recorded VEPs in basal condition and after PS in 43 migraineurs patients (19 with and 24 without aura) and 14 healthy volunteers (HV). We compared P100 implicit time and N75-P100 amplitude of baseline VEP with those collected every 20 s up to 200 s after PS. In HV, N75-P100 amplitude significantly decreased 20 s after PS, and recovered subsequently. There was no effect in the migraine groups. In fact, the percentage reduction in N75-P100 amplitude observed at 20s after photostress in MO and MA patients were lower than in HV (MO vs HV P < 0.05, MA vs HV P < 0.05). In migraine, the percentage of amplitude change at 20 s was negatively correlated with number of days since the last migraine attack (r = −0.525, p = 0.02). We documented altered recovery after PS under the influence of imminent attack. Whether present VEP findings are related to the ictal/interictal migraineur susceptibility to abnormal sensory perception, such as visual discomfort, remains to be determined.